Still laughing : a life in comedy, from the creator of Laugh-in - Schlatter, George, 1932-; Macks, Jon (Unnamed Press / Rare Bird, 2023)
"In 1967, producer George Schlatter pitched an idea for a quirky new television show: one inspired by the hippie counterculture, which would take the idea of sit-ins, love-ins, and be-ins, and manifest that politicized, sexualized, consciousness-raising energy into pure comedy. Much to the surprise of NBC executives, Laugh-In soon became the #1 show on American TV, and the careers of beloved stars like Lily Tomlin and Goldie Hawn were born. Still Laughing features never-before-told stories from the creation of one of the most groundbreaking shows in television history. It also recounts the coming-of-age of one of Hollywood's most iconic producers, from his early nightclub days rubbing elbows with mob figures like Mickey Cohen and John Stompanato, to his influential friendships with Judy Garland and Frank Sinatra, for whom George was asked to deliver a eulogy at his funeral decades later. An inside look at Hollywood in the wake of the cultural upheaval of the '60s and '70s, Still Laughing demonstrates the crucial, deeply creative role a working producer plays in bringing a show (and its stars) to life. With spit-fire humor, tireless wit and keen perception, Still Laughing tells of the rise of some of comedy's greatest talents, and reveals the actual people cloistered inside larger-than-life celebrity."--Publisher's website.